Reflections on the Impact of the New Economic, Sociological and Historical Institutionalism in Institutional Social Policy - José G. Vargas-Hernandez (Journal of Economics and Political Economy, 2014)
This paper intends to make a reflection and analysis of the impact of theoretical and methodological frameworks of reference on different neo-institutional approaches in social policy. The paper questions the functionality and continuity of the institutions that are responsible for the functions of designing and implementing programs of social policy, given the profound changes on the environment of economic globalization processes. The method used primarily focuses on critical analysis and reflection. It is concluded that the institutions of welfare and social security must develop the technological, organizational and administrative skills to create and maintain institutional effects that go beyond being conductive to efficiency, effectiveness and equitable development.
Keywords: B25; B52; H42; H51; I18; I28; 330; Institutions; New institutional economics; Social policy